A Systems Approach to Performance Analysis in Women’s Netball: Using Work Domain Analysis to Model Elite Netball Performance - Mclean, Scott; Hulme, Adam; Mooney, Mitchell; Read, Gemma J. M.; Bedford, Anthony; Salmon, Paul M. (Frontiers in Psychology, 2019)
Netball is a newly professional women’s sport, as such there has been little research conducted investigating performance analysis (PA) in elite netball. The aim of this study was to develop a model of the netball performance system to identify the components of elite performance in netball, and the interactions and relationships between them. Eleven elite subject matter experts (SMEs) participated in workshops to produce a systems model of the netball match performance system. The model was produced using the Cognitive Work Analysis (CWA) framework. A model of the netball match performance system was produced showing the interrelated objects, processes, functions, values and purposes involved in elite level netball matches. The model identified the components of elite level netball performance and the interactions and relationships between them. The model was subsequently used to identify novel PA measures including passing and possession measures, measures of cognitive performance, and measures related to physical activity. Netball is a complex sport, involving multiple dynamic and interrelated components. Consequently, there is an opportunity to develop holistic PA measures that focus on interacting components, as opposed to components in isolation.